2017
DOI: 10.3171/2016.9.jns161585
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing of stereotactic radiosurgery treatment of melanoma brain metastases treated with ipilimumab

Abstract: OBJECTIVE Melanoma represents the third most common cause of CNS metastases. Immunotherapy has evolved as a treatment option for patients with Stage IV melanoma. Stereotactic radiosurgery (SRS) also elicits an immune response within the brain and may interact with immunotherapy. The authors report on a cohort of patients treated for brain metastases with immunotherapy and evaluate the effect of SRS timing on the intracranial response. METHODS All consecutively treated melanoma patients receiving ipilimumab and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 45 publications
3
62
1
1
Order By: Relevance
“…This result suggests that GKRS is a safe irradiation procedure for brain metastases from malignant melanomas, which is consistent with past reports of SRS for brain metastases [42]. However, the outcomes obtained in this series also showed that combining SRS with immune checkpoint inhibitors significantly increased the incidence of radiation injury, which supports results obtained in several prior studies [1,17,18,30,31,34,43,44]. We hypothesized that this observation might be attributable to the increased radiosensitivity of brain tumors, leading to subacute inflammatory changes and lymphocyte toxicity, as described in recent reports focusing on the novel systemic agents [1,17,18,31,32,35].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result suggests that GKRS is a safe irradiation procedure for brain metastases from malignant melanomas, which is consistent with past reports of SRS for brain metastases [42]. However, the outcomes obtained in this series also showed that combining SRS with immune checkpoint inhibitors significantly increased the incidence of radiation injury, which supports results obtained in several prior studies [1,17,18,30,31,34,43,44]. We hypothesized that this observation might be attributable to the increased radiosensitivity of brain tumors, leading to subacute inflammatory changes and lymphocyte toxicity, as described in recent reports focusing on the novel systemic agents [1,17,18,31,32,35].…”
Section: Discussionsupporting
confidence: 83%
“…A high incidence is reported in Caucasians, with malignant melanoma being the third most frequent primary cancer, following lung and breast cancers. Australia, New Zealand, Europe, and the USA have high incidences of 15-20 per 100,000, while malignant melanoma remains rare in Japan at an incidence of 2 per 100,000 [17,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis of patients treated for brain metastases of malignant melanoma revealed that inhibition of the PD-1 axis was more effective than inhibition of CTLA-4 in combination with external beam radiotherapy and that concurrent dosing (at least 4 weeks within the two treatments) was necessary to induce best responses [163]. Independent retrospective studies and one meta-analysis confirmed these results [145,[164][165][166][167][168][169][170][171] (Table 4), also showing the superiority of combining radiation with PD-1 inhibitors compared to combination with other agents such as v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) or dual specificity mitogen-activated protein kinase kinase (MEK) inhibitors [172,173] (Table 4). One retrospective study showed longer overall survival of patients irradiated more than 16 weeks after initiation of ipilimumab, compared to patients irradiated within 16 weeks of starting ipilimumab treatment [174].…”
Section: Current Clinical Insights On Irradiation and Immune Checkpoimentioning
confidence: 95%
“…Several studies have reported better outcomes after treating metastatic brain melanoma with combination radiosurgery and immunotherapy [221,222]. One downside to this treatment is the inflammatory response may be overactive resulting in elevated peritumoral edema and more severe neurologic symptoms [190,191]. Efficacy and safety of concurrent SRS and immunotherapy needs further investigation.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%